'De novo' and 'recurrent' autoimmune hepatitis after liver transplantation: A comprehensive review. (January 2016) - Kerkar, Nanda; Yanni, George
Abstract: Autoimmune Hepatitis (AIH) is a chronic progressive inflammatory disease of the liver that responds to immunosuppressive therapy. In patients with AIH who have an acute liver failure presentation or those who develop end stage liver disease despite medical therapy, liver transplantation (LT) may become necessary. Despite good outcomes after LT, AIH can develop/recur in the allograft with an estimated incidence of recurrence between 8 and 12% at 1 year and 36–68% at 5 years. The presence of non-organ specific autoantibodies, elevated serum aminotransferases and immunoglobulin G as well as the characteristic histologic features of interface hepatitis (peri-portal plasma cell infiltration) characterize recurrence of disease. De novo AIH is the development of features of classical AIH in the allograft of patients who have not been transplanted for AIH. There are several reports in the pediatric transplant population, where administering immunosuppressive therapy in the regimen used to treat AIH has stabilized graft function in de novo AIH. In adults, hepatitis C (HCV) is the most common indication for LT and HCV often recurs after LT, requiring treatment with Interferon and Ribavirin. Labeling the graft dysfunction 'de novo AIH' can be problematic in this context, particularly if HCV RNA is positive at that time. Some have chosen to give other names like 'graft dysfunction mimicking AIH' and 'plasma cell hepatitis'. Regardless of the nomenclature, autoimmune liver graft dysfunction, if managed appropriately with the treatment regimen used to treat AIH, can save grafts and patients. The mechanism causing recurrent or de novo AIH after LT remains unknown. Several mechanisms have been implicated in this loss of self-tolerance including impaired thymic regulation, impaired activity of T regulatory cells, molecular mimicry, calcineurin inhibitors, glutathione-s transferase and genetic polymorphisms. While the phenotype of de novo AIH in pediatrics has been uniform, it has been more variable in adults, highlighting the need for uniform diagnostic criteria or scoring system post LT. Better understanding of the development of autoimmunity and its difference from classical rejection after LT will allow better therapeutic strategies and improved outcome. Highlights: Autoimmune liver disease after transplantation can be 'recurrent' or 'de novo'. De novo AIH implies development of AIH in patients not transplanted for AIH. Phenotype of de novo AIH appears more uniform in pediatrics than adults. Early identification of AIH after liver transplantation and prompt use of the regimen to treat AIH can help save grafts and patients. Further research is necessary to identify mechanisms leading to de novo and recurrent AIH.